2020
DOI: 10.32479/ijefi.10223
|View full text |Cite
|
Sign up to set email alerts
|

How Sukuk and Conventional Bond Affect Economic Growth? Evidence From Indonesia

Abstract: This study is aimed to show how big the impact of sukuk and conventional bond toward Indonesia's economic growth in the period of 2011-2019 by using ARDL method to observe the impact on the short term and long term. The result of this study shows that on the short term, sukuk does not affect the economic growth and bonds affect the economic growth. As on the long term, sukuk affects the economic growth and bonds do not affect the economic growth. This shows that Indonesian people see sukuk better than conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Sukuk has proven to have a positive effect, which means that if there is an increase in Sukuk, it will increase the inclusiveness of economic development in Indonesia. The results of this study are in line with previous studies by (Smaoui & Khawaja, 2017); (Ledhem, 2020); (Kartini & Milawati, 2020); and (Tan & Mohamad Shafi, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Sukuk has proven to have a positive effect, which means that if there is an increase in Sukuk, it will increase the inclusiveness of economic development in Indonesia. The results of this study are in line with previous studies by (Smaoui & Khawaja, 2017); (Ledhem, 2020); (Kartini & Milawati, 2020); and (Tan & Mohamad Shafi, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In the context of Southeast Asia, (Ledhem, 2020) demonstrated that Sukuk financing is boosting economic growth in Southeast Asia, which mirrors the significant part of the Islamic financial markets of Sukuk as a vigorous contributor to economic growth. Furthermore, (Kartini & Milawati, 2020) elaborated a comparative study between Sukuk and conventional bonds in Indonesia linked to economic growth. Using an ARDL (Auto-Regressive Distributed Lag) method, they experimental the effect of Islamic bond (Sukuk) on short-and long-term economic growth.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the ARDL cointegration regression technique has been used to assess the long-and short-term cointegration between Islamic financial development and economic growth (Pesaran et al, 2001). Consistent with the studies of Kartini and Milawati (2020), Orhan and Tirman (2021) and Fuadi et al (2022), ARDL is the most preferred model over other co-integration techniques for many reasons. First and foremost, the ARDL model simultaneously estimates the long-and short-run coefficients.…”
Section: Econometric Modelmentioning
confidence: 92%
“…In the scarce literature on the Islamic bond and economic growth, the studies of Kartini and Milawati (2020) and Setianingsih and Widyastuti (2020) have identified the contribution of Sukuk to the economic growth of Indonesia. Both studies found that in the long run, Sukuk positively influences the economic growth, but in the short run, Sukuk has an insignificant and negative correlation with the economic growth.…”
Section: Islamic Bond and Economic Growthmentioning
confidence: 99%